Functional and aesthetic evaluation of sacrococcygeal teratomas. Not everything ends with surgery - Vanesa Villamil; Oscar Girón Vallejo; María Fernández-Ibieta; Ángela Sánchez Sánchez; Paulo Y. Reyes Ríos; Irene Martínez Castaño; Javier Rojas-Ticona; Ramón Ruiz Pruneda; José I. Ruiz Jiménez (Elsevier, 2018)
Introduction: Sacrococcygeal teratoma is the most common solid neonatal tumour. The improvement in survival has meant that postoperative sequelae can be diagnosed and treated. The aim of this article is to evaluate the long-term outcomes of patients treated in our centre. Material and methods: Records of patients treated for a sacrococcygeal teratoma in our hospital from 1977 to 2014 were retrospectively reviewed. Personal data was collected and a telephone questionnaire was used to assess long-term bowel and urinary habits, as well as an aesthetic and functional self-assessment. Results: A total of 14 patients were treated during the study period, of whom 11 were females and 3 males, with a mean age at the time of the survey of 17 years (8 months to 37 years). Eight patients completed the questionnaire (57.1%). The mean age of the 8 patients was 23 years (4-37 years), of whom 37.5% were operated on due to a sacrococcygeal teratoma type I, 25% type II, 25% type III, and 12.5% type IV. Two of them (25%) had constipation, and one (12.5%) had faecal incontinence. Two (25%) patients suffered from recurrent urinary tract infections, and 3 (37.5%) patients had urinary incontinence. Five patients (62.5%) had a perception of being physically impaired, with limitation of their social life. Conclusions: The incidence of constipation does not differ from that found in the literature. Faecal incontinence is slightly improved compared to what has been published. However, urinary tract infections and incontinence are more prevalent in our series. Five patients out of the eight that responded suffered from psychosocial problems, according to DAS-59 questionnaire. Patients with SCT require urological, bowel, and psychological counselling, until they have a complete functional and emotional development. Resumen: Introducción: El teratoma sacrococcígeo es el tumor neonatal sólido más frecuente. El aumento de la supervivencia de estos pacientes ha permitido diagnosticar y tratar secuelas posquirúrgicas. Evaluamos el resultado funcional y estético a largo plazo de los pacientes intervenidos en nuestro centro. Material y método: Estudio retrospectivo de los teratomas sacrococcígeos intervenidos en nuestro hospital desde 1977 hasta 2014. Se recogieron datos personales de los pacientes y se realizó encuesta telefónica sobre hábito intestinal, urinario y autoevaluación estética y social. Resultados: En el período de estudio se intervino a 14 pacientes, 11 mujeres y 3 varones, con una edad mediana en el momento de la encuesta de 17 años (8 meses-37 años). Se encuestó a 8 pacientes (57,1%). La edad mediana de esos 8 pacientes fue de 23 años (4-37 años). El 37,5% se intervino por un teratoma sacrococcígeo tipo i, 25% tipo ii, 25% tipo iii y 12,5% tipo iv. De los pacientes estudiados, 2 (25%) presentan estreñimiento y uno (12,5%) incontinencia fecal. Dos pacientes (25%) presentan infecciones urinarias recurrentes y 3 (37,5%) incontinencia urinaria. Cinco pacientes (62,5%) presentan alterada su percepción física con limitación en su vida social. Conclusiones: En nuestra serie, se ha encontrado un porcentaje similar a la literatura en la incidencia de estreñimiento. La incontinencia fecal está levemente disminuida respecto a series publicadas. Sin embargo, la frecuencia de infecciones y de incontinencia urinarias es mayor en nuestra serie. Cinco pacientes presentan problemas psicosociales según el cuestionario DAS-59. Los pacientes con teratoma sacrococcígeo requieren asesoramiento urológico, digestivo y psicológico, para poder adquirir un completo desarrollo funcional y emocional.